PENGARUH WORK FAMILY CONFLICT DAN STRES KERJA TERHADAP KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SUKOHARJO - Legowo, Legowo; Wahyudi, Amin; Suprayitno, Suprayitno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This research is conducted to know the significancy between: (1) Work family conflict to the job satisfaction; (2) Job stress to the job satisfaction; (3) Work family conflict to the organizational commitment; (4) Job stress to the wards organizational commitment; (5) Job satisfaction to the organizational commitment; (6) Work family conflict to the organizational commitment with job satisfaction as an intervening variable; (7) Job stress to the organizational commitment with job satisfaction as an intervening variable in the General Official Work And Administration Departement of Sukoharjo The population is the employee of the Department of Public Works and Spatial Planning of Sukoharjo 2019 as many as 139 persons. Samples were taken by cluster random sampling of 60 people. The technique of gathering the data is using inquiry sheet validity test and reliability test. The analysis technique uses double regression with classical assumption. The conclusion of the research; (1) Work family conflict has a negative and significant effect on job satisfaction. (2) Job stress has a negative and significant effect on job satisfaction. (3) Work family conflict has a negative and significant effect on organizational commitment. (4) Job stress has a negative and significant effect on organizational commitment. (5) Job satisfaction has a positive and significant effect on organizational commitment. (6) Job satisfaction mediates the effect of work family conflict on organizational commitment. (7) Job satisfaction mediates the effect of work stress on organizational commitment.